The Significant Impact of Workplace Environment on Gen Z Performance in Indonesia - Hendratmoko; Mutiarawati, Elisabeth Vita (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2023)
Generation Z is currently entering the workforce, and the representation of Gen Z employees is continuously growing in various companies. Individual performance has a direct influence on the success of organizations or companies. Therefore, understanding and addressing the needs of employees, particularly those from Generation Z, have become essential in organizational management. This research aims to analyze the role of the workplace environment in influencing the performance of Generation Z employees. In reality, Generation Z encounters challenges in interpersonal skills. Information technology has also altered the attitudes and behaviors of Generation Z. Despite being intelligent, they may lack maturity at times. They tend to be individualistic and pragmatic, living in a digital era where everything is fast-paced and easily accessible. Hence, this study aims to analyze The Significant Impact of Workplace Environment on Gen Z Performance. This research adopts a quantitative approach, with 100 respondents from Generation Z located in Jakarta. Data collection is conducted through questionnaires, utilizing a non-probability sampling technique. The analysis method employed is Partial Least Squares (PLS), using the SmartPLS 4.0 application. The significance of the findings in this study lies in the fact that among the variables under investigation, the workplace environment is the only factor that significantly influences the performance of Generation Z employees. Meanwhile, the other two variables, workload and job stress, exhibit negative effects on performance, though these effects are not statistically significant. A conducive workplace environment is identified as a key factor in enhancing the performance of Generation Z employees.